Digital Marketing Strategy for Beauty Products Through Beauty Vlogger - Totok Wahyu Abadi; Elviena Fitriana Hawa (Universitas Muhammadiyah Sidoarjo, 2023)
The phenomenon of beauty vloggers on social media as influencers and brand ambassadors for beauty products has become a trend and popular culture in Indonesia. This study aims to analyze and reveal how the online promotion strategy for Scarlett Whitening products utilizes the role of beauty vloggers and e-Word of Mouth (e-WOM) on social media in promoting their products and determining consumer purchasing decisions. The method used is quantitative with respondents using Scarlet Whitening in East Java Province who were determined by simple random sampling technique. The data for this study were questionnaires that were distributed online through social media applications (whatsapp and google form) and were analyzed using multiple linear regression. The results of this study are that the use of digital marketing beauty vlogger strategies and e-Word of Mouth (e-WOM) as influencers and brand ambassadors on social media has a significant influence on purchasing decisions for skincare scarlett whitening products in Indonesia. In addition, there are also several other supporting factors that determine the purchase of beauty products in East Java.